Tectonic Record of Deformation in Intraplate Domains: Case Study of Far-Field Deformation in the Grands Causses Area, France - Oriane Parizot; Yves Missenard; Pierre Vergely; Frederic Haurine; Aurélie Noret; Guillaume Delpech; Jocelyn Barbarand; Philippe Sarda (Geofluids)
Although tectonic plates are usually considered as rigid blocks, intraplate deformation such as lithospheric buckling or diffuse brittle deformation has been recognized for a long time. However, the origin of these deformations remains puzzling. Indeed, whereas the chronology of deformation at plate boundaries can be constrained by numerous methods (syntectonic sedimentary record, thermochronology, etc.), dating of brittle structures (faults, veins, and joints) in the far-field domains remains challenging, preventing a global interpretation of the system as a whole. In this contribution, we have combined a tectonic study with a synkinematical geochronological study of fault-related calcites of the Grands Causses intraplate domain, north of the Pyrenean orogeny. We show that these faults record a much longer history of deformation than previously thought. The Mesozoic extension, usually attributed to an early Jurassic Tethysian rifting event, probably lasted until the Barremian-Aptian epoch, in response to the Pyrenean basin’s opening. The so-called “Pyrenean deformation” of the Grands Causses domain, usually associated with the paroxysm of deformation in the belt during the late Eocene, began much earlier, around 100 Ma, and lasted for more than 60-70 Ma. This study demonstrates the high sensitivity of an intraplate domain (Grands Causses area) to record extensional or compressional deformations occurring at the edge of neighbouring plates.